Associations between Inadequate Parenting Practices and Behavioral Problems in Children and Adolescents with Attention Deficit Hyperactivity Disorder - Maria Cristina Triguero Veloz Teixeira; Regina Luisa de Freitas Marino; Luiz Renato Rodrigues Carreiro (The Scientific World Journal)
Children and adolescents with ADHD present behaviors such as impulsiveness, inattention, and difficulties with personal organization that represent an overload for parents. Moreover, it also increases their level of stress and leads them to resort to inadequate educational strategies. The present study verifies associations between inadequate parenting practices and behavioral profiles of children and adolescents with ADHD. The sample was composed of 22 children with ADHD (age range 6–16 years) and their mothers. Spearman correlation analyses were made with the scores of Parenting Style Inventory (PSI) and Child Behavior Checklist for ages 6–18 (CBCL/6–18). Results indicate statistically significant associations between behavioral problems and the use of punishment practices and negligence. When assessing a child with ADHD, it is important to verify the predominant types of parenting practices that can influence both immediate interventions and the prognosis of the disorder.